DESIGNING ACCESSIBLE TOURISM EXPERIENCES: SLOW, SENSORY AND SMART FRAMEWORK - Dora Agapito; Manuela Guerreiro (Enlightening Tourism: A Pathmaking Journal)
Slow tourism is an emergent research area focused on slowing the pace of life during vacations. A comprehensive multi-sensory approach can contribute to designing enhanced slow tourism experiences deemed accessible, both in situ and remotely. There is a research gap in considering multi-sensory stimuli in the design of accessible tourism experiences using technology. As such, this research intends to propose a theoretical framework focused on the development of slow tourism through sensory cues and smart technologies. In so doing, a critical approach to literature was carried out by intersecting three areas of literature following the rationale of the Stimuli-Organism-Response model: slow tourism, multi-sensory tourism experiences design, and smart destinations. The significance of this framework is threefold: it strengthens local identities and aids sustainable tourism by involving the community; it promotes experiences deemed authentic considering multiple stakeholders’ perspectives; and it addresses the visitor experience before, during and after the visit to the destination in an accessible manner using smart technologies. A framework with six steps is offered based on participatory methods.